The Evaluation of Arabic Textbook "Terampil Bahasa Arab 1" Class X Islamic Senior High School Based on Curriculum 2013 - Nur Hayati; Kamal Yusuf (Journal of Arabic Language Studies and Teaching, 2021)
This study examines the 2013 curriculum material by researching the textbook "Terampil Bahasa Arab 1 Class X Senior High School Based on Curriculum 2013" published by AQILA publisher. The book contains a curriculum based on competence and educational character in learning Arabic. The main objective in the discussion of this article is to determine the quality of the 2013 curriculum-based learning books. Researchers used a scientific approach. The method used is descriptive qualitative which focuses on aspects of understanding quality in depth in mufradat texts as well as supporting aspects of 2013 curriculum-based learning books. consistency and gender bias in some mufradat. In the design aspect, the choice of colours to subdue is still lacking because it affects the quality of reader interest.